“Overcoming the Fear That Haunts Your Success” – The Effectiveness of Interventions for Reducing the Impostor Phenomenon - Zanchetta, Mirjam; Junker, Sabine; Wolf, Anna-Maria; Traut-Mattausch, Eva (Frontiers in Psychology, 2020)
The impostor phenomenon (IP) refers to intense thoughts of fraudulence reported by high-achieving individuals. Since it has been shown to account for several personal and work-related complications, effective interventions are greatly needed. Against the background of mindset theory, we developed and tested two mindset interventions. We evaluated the impact of a coaching and a training intervention adopting a randomized controlled outcome design. One hundred and three young employees were randomly assigned to receive coaching (n = 36), training (n = 33), or no intervention (n = 34). Results reveal that coaching was an effective mindset intervention for sustainably reducing IP scores. Fear of failure emerged to mediate the relation between the coaching intervention and the reduced IP scores significantly. Moreover, coaching improved self-enhancing attributions and self-efficacy and reduced the tendency to cover up errors as well as the fear of failure. Training was superior in regard to knowledge acquisition. Specific implications are discussed.